How do early childhood practitioners define professionalism in their interactions with parents?. Issue 2 (4th March 2018) - Ward, Ute
ABSTRACT: This study deepens the understanding of the interactions between early childhood practitioners and the parents of young children in English day care settings, nurseries and pre-schools. Using a phenomenological approach and semi-structured interviews with 17 experienced practitioners the study highlights practitioners' lived experiences and their conceptualisation of relationships with parents. A shared definition of professionalism in these interactions does not emerge. However, a model is developed which includes three dimensions practitioners use to describe their professionalism in their relationships with parents. It becomes apparent that practitioners' attitudes and approaches to their work with parents are varied and highly individual with an indication that they change with experience. This leads to the recommendation of support for all pre-service and in-service practitioners to reflect on the practitioner–parent relationship alongside the consideration of each child's development and learning.